New Devonian gastropod genera important for paleographic reconstructions - Blodgett,R.B.; Fryda,J. (Journal of the Czech Geological Society, 1999)
Twelve new Devonian gastropod genera are established in this paper which we deem important in better delineating Devonian biogeographic units. New genera include: Semilukispira, Teutonophon, Goldfussoceras, Manitobiella, Ibergia, Humboldtiella, Paragnesia, Winterbergiella, Spiniplatyceras, Roemeriella, Devononerita, and Dahmeria. In addition, one new Silurian genus, Ornatosinuitina, is established
Keywords: Paleozoic; Gastropoda; Devonian; new taxa